The factors that influence business losses: a case study for Syarikat Air Melaka Berhad / Baizura Abu Bakar - Abu Bakar, Baizura (Faculty of Business and Management, 2011)
This study about there are many cases of water theft and illegal connections often occur. Not only SAMB Water Company but each state also would have this problem. Such a problem is actually one of the factors which he led the organization facing problem of losses in their business activities. In addition, SAMB is a single water company operating in the distribution of water supply to all of Melaka without competing with any other side. Due it does not compete with any other party; they have to incur losses in the act of those who are responsible for taking advantage to steal the water and making illegal connections. This is likely due to factors such as light punishment measures, management of the SAMB in discharging their duties and technologies available in the SAMB. Studies performed on SAMB may help to alleviate the problem of water theft and illegal connections.